Caracterización de accesiones de chile (Capsicum spp.) - Martín, Nora C.; González, William G. (Agronomía Mesoamericana, 2016)
A population of 59 accessions of pepper (Capsicum spp) from the Germplasm Bank ofthe Centro Agronomico Tropical de Investigacion y Ensenanza (CATIE) and two populations from the Genetic Resources Program of the Vniversity of Costa Rica (UCR) were evaluated. Field experiments were conducted at the Fabio Baudrit UCR Experiment Station in Alajuela. Trials were conducted during the months of January through September of 1989. Seedlings were established under greenhouse conditions and later transplanted in the field. The populations were characterized with data obtained from field experiments. Various quantitative and qualitative characteristics were related to one another using simple linear correlations. Qualitative characteristics were related using the Engel’s equation. Pulp thickness was positively correlated with fruit fresh weight (r=0.75), seed number (r=0.59) and fruit length (r=0.53); and negativelycorrelated with pungency (r=-0.42) and days to flower (r=-0.36). Fruit diameter was posit’ively correlated with seed number (r=0.62) and pulp thickness (r=0.72). Pulp thickness also was positively correlated with seed number (r =0.51). Using the relationships proposed by Engels, 21 pairs of characteristics were related. For example, the majority of the heaviest fruits were positively correlated with early maturing white flower plants.